MODEL PENGAMBILAN KEPUTUSAN BERBASIS KOLABORATIF DI LEMBAGA PENDIDIKAN RAUDLATUL ATHFAL - Sa'diyah, Halimatus; Kamaria, Kamaria; Mubarok, Ramdanil; Harwisaputra, Andreas Fredyansa; Tasbih, Tasbih; Azahra, Salsabila (MPI STAI Sangatta Kutai Timur, 2024)
Collaborative decision-making is an important element in educational management, especially in Raudlatul Athfal (RA) institutions, which have complex needs from various parties. This study aims to analyze the collaborative decision-making model at Raudlatul Athfal PIQ Sangatta Utara, focusing on the implementation process, benefits, and challenges faced. This study employs a qualitative approach, utilizing a case study method. Data were collected through in-depth interviews, participant observation, and document analysis and then analyzed using the Miles and Huberman interactive model. The study results indicate that the collaborative decision-making model involves the active participation of the principal, teachers, parents, and school committee in the strategic policy-making process. This approach has succeeded in increasing a sense of shared ownership, strengthening communication, and producing decisions that are more responsive to the needs of the institution and stakeholders. Other benefits identified include increased management effectiveness, quality of education services, and satisfaction of related parties. The implementation of this model faces several challenges, such as differences in interests between stakeholders, limited managerial capacity, and resistance to changes in organizational culture. The researcher recommends a strategy to strengthen participatory management capacity, improve communication between parties, and provide continuous training for decision-makers in educational institutions.